Attachment of Campylobacter jejuni on biofilms from two chicken houses in Thailand - Daungjinda, M.; Trachoo, N.; Kunyaboon, S. (Songklanakarin Journal of Science and Technology (SJST), 2007)
The attachment of C. jejuni on four gram negative biofilms (FBRL-C04, FBRL-B05, FBRL-F01 and FBRL-B06) isolated from two chicken houses were studied. It was found that C. jejuni attached to biofilm of FBRL-F01 at the highest rate (4.4 logCFU/cm2) compared (P<0.05) to FBRL-C04 FBRL-B05 and FBRL-B06 (4.0 4.0 and 4.1 logCFU/cm2, respectively). Coaggregation between C. jejuni and biofilm organisms may indicate the ability of organisms to form biofilm together. Percent coaggregation between C. jejuni and biofilm organisms, FBRL-C04 and FBRL-F01 was 39.14% and 33.70%, respectively, higher (P<0.05) than thatwith FBRL-B05 and FBRL-B06 (-3.38% and 12.87%, respectively). Hydrophobicity of planktonic and biofilm cells of C. jejuni and 4 biofilm producers were measured by the microbial adhesion to hydrocarbon (MATH) method using hexadecane. FBRL-B06 showed the highest (P<0.05) hydrophobicity (68.95%) indicating more hydrophobic components on its cell surface. Planktonic cells had lower (P<0.05) hydrophobicity than biofilm cells. However, the degree of hydrophobicity of biofilm cells was not related to attachment of C. jejuni on biofilms.